Drivers and consequences of work-family conflict for work from home employees: a systematic literature review - Alias, Siti Noormi; Annuar, Nursyamilah; Mohd Anuar, Mohd Ashraf; Abdul Rahman, Segufta Yasmi; Ismayatim, Shafareeza; Hashim, Mohd Shukri; Subramaniam, Sarada Devi R. (RSIS International, 2024)
The changes in the nature of work-nonwork boundaries due to work-from home practices may results in potential shocks to role conflict among working married couples. However to date, there are still limited understanding of the prevalence of work-family conflict (WFC) among employees while working from home. Therefore, there is a need to explore regarding the stated issue. This systematic literature review has been conducted to figure out what have been found from past studies. This study echos the SLR steps proposed by Xiao and Watson (2019) to search for drivers and consequences of work-family conflict while working from home supported by Work-Family Border Theory and Work-Family Enrichment Theory. From 15 articles found from Google Scholar database, only 11 articles deemed suitable for further consideration. Analysis of the articles resulted in three categories of WFC drivers, which include personal factors, health-related factors, and job-related factors and three categories of consequences found, personal, social, and job outcomes. Findings of this study therefore are expected to be a value to scholars, community and nation as it will provide a new insight to the field.